Pesan Dakwah Moderasi Beragama Dalam Program Muslim Travelers NET TV Tahun 2020: (Analisis Tayangan Komunitas Muslimah Di Irlandia) - Moh. Khoirul Fatih, Khoirul Anam (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2020)
Religion seems to be the last resort for people to escape from the existing problems of social life. Religions is also a belief system that people believe in. Si there are many ways to abtain religious knowledge and also ways to manifest in everday life internal problems that plague Muslims today include the existence of an exclusive religious movement which other Muslims call due to differences in views. Another problems faced by Muslims is the exsistence of Muslims groups who commit acts of violence, as if religion is used as a recommendation letter to commit acts of violence against other groups. The phenomenon of religious moderation displayed in the Muslim Travelers program s a way for the television industry in this case NET TV to provide religious messages that are more inclusive and prioritize social values as a pillar in shapping world peace.